Autotransplantation for the management of ketamine ureteritis. (9th April 2015) - Raison, Nicholas Tobias Johannes; O'Brien, Timothy; Game, David; Olsburgh, Jonathon
Abstract : Ketamine-associated cystitis is a well-recognised syndrome; yet upper urinary tract involvement remains poorly understood. We present the case of a 33-year-old man who developed ketamine-associated cystitis and ureteritis. The patient's severe bladder symptoms required subtotal cystectomy and orthotopic reconstruction. However, the associated ureteritis led to bilateral ureteric obstruction and renal failure. Bilateral autotransplantation with pyelovesicostomy was performed. This first case of autotransplantation for ketamine uropathy helps to demonstrate the potentially devastating effects of ketamine on the urinary tract.